A simple and efficient wavelet approach for evaluating surface integral over curved domain - T. Shivaram, K.; Kiran, S. (International Journal of Engineering and Technology, 2018)
This paper presents, a simple and efficient wavelet approach for computing the surface integrals over irregular or curved dom ain, the limit of the integrals are nonlinear function are transformed to standard two square by using finite element basis function, Haar wavelet based integration technique is applied to evaluation of surface integral over curved domain, the computational efficiency of the method is illustrated with several numerical examples.Â